2021
DOI: 10.1002/jmv.26842
|View full text |Cite
|
Sign up to set email alerts
|

The genotype distribution and phylodynamic of measles viruses circulating in the east of China in postvaccine era, 2005–2017

Abstract: The increase of the evolutionary pressure will cause phylodynamics changes of viruses. In post‐vaccine coverage era, measles viruses face more immune pressure than ever before. Vice versa, the phylodynamic changes may reflect herd immunity level provided by vaccination. In this study, we analyzed phylodynamic characteristics of measles viruses isolated from 2005 to 2017 in Jiangsu province of China using nucleoprotein gene sequences of measles viruses. The phylogenetic tree was constructed with Markov chain Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The TMRCAs of MeV N gene in Shandong are consistent with those in China, and the mean evolutionary rate of MeV N‐450 (1.267 × 10 −3 substitutions/site/year) is relatively high, 39 which can be explained by the fact that the N‐50 is one of the most variable regions across the whole genome. However, a declining trend was found in gene distance of the N gene with time, which may reflect the interruption of pre‐existing viruses transmission under immunity pressure 40 . With the substantial emergence of major divergent clades of H1, the genetic diversity of MeV N gene in Shandong increased before 2005, which may be related to the outbreaks of measles in Shandong Province at those times, and similar result was reported in a previous study, which showed that MV N gene genetic diversity displayed an increase between the 1970s and 2000 16 .…”
Section: Discussionmentioning
confidence: 95%
“…The TMRCAs of MeV N gene in Shandong are consistent with those in China, and the mean evolutionary rate of MeV N‐450 (1.267 × 10 −3 substitutions/site/year) is relatively high, 39 which can be explained by the fact that the N‐50 is one of the most variable regions across the whole genome. However, a declining trend was found in gene distance of the N gene with time, which may reflect the interruption of pre‐existing viruses transmission under immunity pressure 40 . With the substantial emergence of major divergent clades of H1, the genetic diversity of MeV N gene in Shandong increased before 2005, which may be related to the outbreaks of measles in Shandong Province at those times, and similar result was reported in a previous study, which showed that MV N gene genetic diversity displayed an increase between the 1970s and 2000 16 .…”
Section: Discussionmentioning
confidence: 95%